Assessment of sleep quality in severe covid-19 hospitalized patients - Abbasi, Nida Zeb; Baig, Kainaat; Muhammad Hassan; Syed, Fibhaa; Waheed Jami, Muhammad Anas; Usman, Muhammad (Journal of the Pakistan Medical Association, 2024)
Objectives: To evaluate the quality of sleep in patients hospitalised with coronavirus disease-2019, and its impact on hospitalisation duration, need for intensive care unit admission and mortality. Methods: The cross-sectional study was conducted at the Pakistan Institute of Medical Sciences, Islamabad, Pakistan, from May 2, 2021 to April 30, 2022, and comprised hospitalised coronavirus disease-2019 patients. Data was gathered using the Pittsburgh Sleep Quality Index questionnaire, including demographics, comorbidities, length of hospital stay, need for intensive care unit admission, C-reactive protein and D-dimer values at admission, and the outcome. The patients were divided into group A having good sleep quality score >5 and group B having poor sleep quality score <5. Data was analysed using SPSS 25. Results: Of the 1,250 patients, 559(44.7%) were males and 691(55.3%) were females. There were 560(44.8%) patients in group A with mean age 53.80±14.85 years, and 690(55.2%) patients in group B with mean age 53.71±14.32 years. There were no significant intergroup differences in terms of age and high-resolution computed tomography scan (p>0.05). The difference was significant with respect to gender, comorbid conditions, education status as well C-reactive protein and D-dimer levels (p<0.001). Group B patients had a longer duration of hospitalisation (p<0.001) and a higher need for intensive care unit admission (p<0.001) compared to group A. The outcome was death in 166(13.28%) patients in group B compared to 40(3.2%) in group A (p<0.001). Conclusion: Poor sleep quality was found to be associated with longer hospital stay, increased need for mechanical ventilation, and higher mortality rate in coronavirus disease-2019 patients. Key Words: Sleep condition, Covid-19, PSQI.